2002
DOI: 10.1111/j.1749-6632.2002.tb04317.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin Gene VNTR Polymorphism with Polycystic Ovary Syndrome

Abstract: Variability in the number of tandem repeats of the insulin gene (INS VNTR) is known to influence several phenotypes, including polycystic ovary syndrome (PCOS), diabetes mellitus type 1, diabetes mellitus type 2, and birth weight. The presence of the class III allele of INS VNTR has been reported to be protective in diabetes mellitus type 1, but in contrary it increases the disease risk of PCOS and diabetes mellitus type 2. PCOS is a very common endocrinopathy in women of reproductive age. The etiology of PCOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…Moreover, paternal transmission of class III alleles from heterozygous fathers to anovulatory patients with PCOS was more frequent than was maternal transmission (38,39). However, later case-control studies did not confirm these associations (7,40,41).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, paternal transmission of class III alleles from heterozygous fathers to anovulatory patients with PCOS was more frequent than was maternal transmission (38,39). However, later case-control studies did not confirm these associations (7,40,41).…”
Section: Discussionmentioning
confidence: 81%
“…The issue of b-cell function in PCOS remains even more controversial, with findings ranging from increased to defective insulin secretion (2)(3)(4)(5)(6)(7)(8). Genetic factors determine not only insulin resistance but also, and probably more strongly, insulin secretion (9).…”
mentioning
confidence: 98%
“…Our initial search identified a total of 476 potentially eligible articles. Based on our inclusion criteria, a total of 8 articles were involved in this meta-analysis [10,[12][13][14][15][16][17][18]. There was perfect inter-rater reliability for the selection of studies to be included in the meta-analysis, with Kappa values of 0.834 based on titles and abstracts and 0.857 based on full texts.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Another family-based study also showed that PCOS was associated with the III alleles [11]. In addition, numerous genetic associated studies with case-control design have focused on the association of INS VNTR and POCS [10,[12][13][14][15][16][17][18]. However, results of different studies have been inconsistent, suggesting that it is unclear whether INS VNTR is associated with PCOS or not.…”
Section: Introductionmentioning
confidence: 97%
“…In total, 13 case-control studies [21][22][23][24][25][26][27][28][29][30] including 1,767 cases and 4,181 controls, were included in the analysis. Waterworth DM [21] and Powell BL [23] were conducted on the anovulatory PCOS.…”
Section: Baseline Characteristicsmentioning
confidence: 99%